+0  
 
0
111
3
avatar

QUESTION 1 - PART A

 

If \(x^2 - 7x + c = (x + a)^2 \) for some constants is a and c, then find a.

 

QUESTION 1 - PART B

 

If \(x^2 - 7x + c = (x + a)^2 \) for some constants is and c, then find c.

 Jan 12, 2021
 #1
avatar+843 
0

Hi Guest!

 

Question 1 - Part A

First, let's start by expanding the (x + a)^2 part of the question. 

(x + a)^2 = x^2 + 2ax + a^2

We can then replace it. 

x^2 - 7x + c = x^2 + 2ax + a^2

We can quickly see that a = -3.5 since 2a = 7. 

 

Question 1 - Part B

We can also see that c = a^2. 

c = (-3.5)^2

c = 12.25

 

I hope this helped. :)))))

 

=^._.^=

 Jan 12, 2021
 #2
avatar
+1

THANK YOU!

 Jan 12, 2021
 #3
avatar+843 
0

You're welcome. :DDDDDD

 

=^._.^=

catmg  Jan 12, 2021

20 Online Users

avatar
avatar